Analysis of miR-155 Expression in Prostate Cancer Patients - Habibi, Sanaz; Rouhi, Vahid; Baykal Koca, Sevim; Köseoğlu, Hikmet; Güven, Mehmet (Cerrahpaşa Medical Journal, 2025)
Objective: Prostate cancer is a major global health issue and the second most common cancer in men. Its pathogenesis involves genetic and epigenetic changes, hormonal imbalances, and environmental factors, with deficiencies in double-strand break repair mechanisms playing a critical role. microRNAs (miRNAs) are small, non-coding RNA molecules that regulate gene expression post-transcriptionally and are implicated in cancer-related processes. Methods: microRNA-155 expression was analyzed in paired tumor and normal tissues from 50 patients with pathologically confirmed prostate cancer (PC) using quantitative reverse transcription polymerase chain reaction (qRT-PCR). In addition, clinical parameters such as age, smoking status, diabetes, hypertension, PIRADS scores, and Gleason scores were evaluated for their potential association with miR-155 expression. Results: No statistically significant difference was observed in miR-155 expression between tumor and normal tissues (P > .05). Moreover, miR-155 levels did not show significant correlation with any of the evaluated clinical factors. Conclusion: These findings suggest that miR-155 may not play a direct role in the development and progression of PC. However, this study contributes to the growing understanding of the relationship between PC, DNA repair mechanisms, and miRNA regulation. Further studies with larger cohorts and standardized methodologies are needed to clarify the potential of miR-155 as a biomarker or therapeutic target in PC. Cite this article as: Habibi S, Rouhi V, Baykal Koca S, Köseoğlu H, Güven M. Analysis of miR-155 expression in prostate cancer patients. Cerrahpaşa Med J 2025, 49, 0008, doi: 10.5152/cjm.2025.25008.